Dyke-Davidoff-Masson Syndrome - Koirala, Naba Raj; Khadka, Roshana; Bhattarai, Manoj; Tulachan, Dibya; Das, Ajay Kumar; Poudel, Jwalanta (Journal of Nobel Medical College, 2012)
Dyke-Davidoff-Masson Syndrome (DDMS) is characterized by seizures, facial asymmetry, contralateral hemiplegia and mental retardation. The characteristic radiologic features are cerebral hemiatrophy with homolateral hypertrophy of the skull and sinuses. Here we report a case of a 16 years young girl who presented with seizures severe mental retardation and weakness of left upper-limb and on CT brain was diagnosed to have DDMS.DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7306 Journal of Nobel Medical College (2012), Vol.1 No.2 p.84-86